Growth performance and survival rate of vannamei shrimp (Litopenaeus vannamei) post-larva stages in a super intensive cultivation system with varied densities - Tulas Aprilia; Yoka Agustama; Rakhmawati Rakhmawati; Eulis Marlina (Depik, 2023)
Vannamei shrimp (Litopenaeus vannamei) holds significant economic importance in Shrimponesia as a prominent shrimp commodity. The post-larval stage often encounters challenges, primarily due to the shrimp's limited ability to adapt and survive in a new environment. Stocking density is a crucial factor influencing the growth and production performance of vannamei shrimp culture. This study aims to assess the optimal stocking density for achieving optimal growth and survival in L. vannamei. A 40-day maintenance trial was conducted at UD Mina Rahayu Kalianda to investigate the impact of different stocking densities on water quality in the maintenance media. The study utilized containers with varying stocking densities: treatment A (1 shrimp/L), treatment B (1.5 shrimp/L), and treatment C (2 shrimp/L), each with three replications. The findings revealed survival rates (SR) of 83.33% for treatment A, 62.78% for treatment B, and 58.33% for treatment C. Mean Body Weight (MBW) values were recorded as 1.2592 g/shrimp for treatment A, 1.1216 g/shrimp for treatment B, and 0.7728 g/shrimp for treatment C. Average Daily Growth (ADG) results showed 0.0313 g/shrimp for treatment A, 0.0279 g/shrimp for treatment B, and 0.0192 g/shrimp for treatment C. Based on the study, the recommended stocking density for white vannamei shrimp is 40 shrimp/L, demonstrating improved growth and survival rates for this species.